WELFARE AND THE CRIME OF CORRUPTION IN THE RULE OF LAW - Nazaruddin, Nazaruddin; Ardiyansyah, Amzar; Mahdi, Umar (Proceeding International Seminar of Islamic Studies, 2024)
The crime of corruption has damaged the joints of the life of the nation and state. This disgraceful act is committed by government officials which results in development not running, the economy is low, education and health facilities are not optimal, and most importantly at this time the welfare of the community is still far from expectations because of corruption that occurs at all levels of government both horizontally and vertically. So the problem arises, namely whether corruption has an impact on people's welfare, what is the background of corruption, and how the efforts of the government and law enforcement agencies against corruptors. To obtain these answers, normative research is conducted by examining laws and regulations, books, journals, and other documents related to the research. Corruption that occurs in all sectors of government that causes state financial losses has an impact on the welfare of the community, because infrastructure development, low economy, not maximizing education and health facilities are caused by corruption. Corruption occurs due to political influence and power so that it is easy to commit corruption without being known by the public. efforts made by the government have been made in various ways, namely establishing regulations related to eradicating corruption, including involving the community and providing additional education in every university with anti-corruption education material.